A Pilot Curriculum to Integrate Community Health Into Internal Medicine Residency Training - Catalanotti, Jillian (The Accreditation Council for Graduate Medical Education, 2013)
BACKGROUND: Public health training has become an important aspect of residency education. The Institute of Medicine recommends public health training for all resident physicians, and internal medicine educational milestones include general public health skills. OBJECTIVE: We sought to integrate community health into internal medicine residency training by developing a community health elective (CHE) curriculum. METHODS: We developed a 2-week CHE curriculum for internal medicine residents, featuring facilitated discussion sessions, clinical experience at health centers targeting medically underserved populations, and a culminating presentation. We evaluated our pilot curriculum using pre-elective and postelective course surveys with Likert-type questions. RESULTS: Of 150 eligible residents, 32 (21%) enrolled in the elective. Nearly all participants (30 of 32, 94%) strongly agreed that learning about community health was an important part of their residency training. Residents' perceived competence at discharging hospital patients with follow-up at community health sites increased 13-fold after taking the elective (P < .001). There was no increase in reported likelihood to practice in an underserved community or in primary care. CONCLUSIONS: The CHE addresses several Accreditation Council for Graduate Medical Education competencies and internal medicine Milestones and could be a replicable model for internal medicine residency programs that seek to provide community health training.